MAKTABAH SYUMILA NU FIHA DAN MAKTABAH SYAMILAH: DIGITAL TRANSFORMATION AND CONTESTATION IN PESANTREN - Kardi Kardi; Al Makin; Anis Masruri (Akademika : Jurnal Pemikiran Islam, 2020)
This article aims to describe the Pesantren’s response to the use of digital applications of classical books as open sources of education. Starting from the phenomenon of using al-maktabah sya> milah software in Pesantren Salaf (traditional Islamic boarding schools) where they have a scientific tradition of using printed Kitab Kuning (Islamic classical books) for quite a long time. The presence of a digital media transformation called al-maktabah sya>milah is an alternative for searching information on classical books in Pesantrens. Then, this article questions on the emergence of al-maktabah syu> mila NU fi>ha software at the Pesantren Assalafiyyah, Mlangi, Sleman, Yogyakarta in response to the presence of al-maktabah sya>milah. Syu>mila NU containing digital books by mu'tabar ulama taught in Pesantren Salaf, while Syamilah containing books by Arabic ulama allegedly carrying Wahhabi understanding. This has led to a contestation between the two Kitab Kuning digital applications in the Pesantren Salaf. This article uses an interpretive qualitative descriptive approach from library document data, multi-site, and software. The author analyzes the information on both the software and the related web. Maktabah syu> mila NU fi>ha software development is defensive which aims to fortify the Pesantren from the influence of the syamilah maktabah understanding which brings Wahhabi; a intolerant, apolitical, anti-tradition, and transnational understanding. The presence of this application appeared various responses from the pesantrens. Pesantren Hidayatul Mubtadi'in Lirboyo, Kediri tends to be skeptical whether Pesantren Assalafiyyah Mlangi, Yogyakarta is more neutral, and Pesantren Salafiyyah Syafi’iyyah Sukorejo, Situbondo tends to be moderate and optimistic. This response is inseparable from the pesantren policy which is contained in the board’s rules for the use of electronic devices.